The Little Man in R. Senchin’s Short Prose of the Late 1990s and Early 2000 - Maria V. Larina (Гуманитарный вектор)
Roman Senchin, a winner of prestigious literary awards and a recognized master of social prose, is one of the most brilliant representatives of the "new realism". The main character of the author’s works is a little man who survives the cataclysms of the late 20th century, losing himself in the historical and social chaos. The author develops this type of character in the novels The Eltyshevs (2009), Flood Zone (2015), Rain in Paris (2018), the anthologies Day Without Number (2006), Moscow Shadows (2009), etc. However, the peculiarities of R. Senchin’s interpretation of the image of the little man were formed in the writer’s early stories.The article offers a classification of the variants of the image of the little man, depending on the author’s goals, based on the material of the stories published in the magazines Znamya, Novy Mir, and Oktyabr in the late 1990s and early 2000s. It reveals the characteristics of the "portrait of the transitional period" created by R. Senchin. The aim of the study is to identify the typical features of the author’s description of the image of the little man in the short prose of this period. The poetics of four representative stories of the author were analyzed by means of motive analysis, compositional analysis, intertextual and narrative methods. The principles of the representation of the little man in connection with the domestic and foreign paradigm of marginal heroes, the trend of "new realism" and its focus on the treatment of traditional images not only of the little man, but also of the superfluous and underground hero are revealed. Specific characteristics of R. Senchin’s artistic world are revealed. A complex descriptive analysis of the stories shows that the author, referring to the classic type of the little man, mercilessly destroys the illusions of his characters, accusing them of passivity and their need for escape from themselves. Senchin’s Little Man is a product of the post-perestroika era, having missed his former opportunities and failed to acquire new ones. However, deprived of the author’s compassion, this type still appeals to the reader’s empathy: behind each, even the most repulsive hero, one can see a human being in general and oneself in particular.